Does a model of care for chronically ill patients exist in the European Union? - Kurpas, Donata (Przewodnik Lekarza/Guide for GPs, 2009)
The prevalence of chronic diseases was analyzed and the most important indicators for the chronic disease management model underlined in European programmes are presented in the paper. The various elements of the models help to better understand healthcare in general practice. The professionalism of the practice team with new roles, task sharing and the implementation of modern strategies for the care of chronically ill patients provides first of all a new chance for family doctors’ practices in the future.